Diversity of Angiospermae Plant Class Liliopsida in Mount Nglanggeran - Bayu Setya Aji Nugraha; Widodo Widodo; Rendi Yuntara; Normalita Normalita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2018)
Nglanggeran is a place that has a high plant diversity and there are many unique and unidentified wild plants. This study aims to list liliopside class plants which found around the climbing route. The angiosperm plants in the liliopside class found around the climbing route were successfully identified and consisted of 40 species belong to 17 families.